Analysis of market positioning and generic strategy map of gelato products in Indonesia market place - M Ali Pahmi; Miftahul Imtihan; Mastang (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2026)
This study investigates the market potential, positioning, and strategic formulation for milk-based gelato products in Indonesia. Literature analysis reveals that ice cream holds a special place among Indonesian consumers, with 69.2% expressing strong preference and only 0.6% disliking it. The Indonesian ice cream market recorded USD 527 million in revenue in 2019, with a CAGR of 15.97% from 2015 to 2019, and consumption volume reaching 105.3 million kilograms. Future projections indicate a continued positive growth trend at a CAGR of 7.18% between 2020 and 2025, driven by rising disposable incomes, urbanization, and lifestyle shifts favoring premium dairy products such as gelato. The market positioning analysis of the top 10 gelato brands shows diverse competitive strategies: Bonico offers the most competitive price per gram, Batavia leads in flavor variety, and Powder Aja and Toffin excel in packaging weight for B2B segments like cafés and restaurants. Furthermore, generic strategy analysis identifies four limitations faced by the industry: high-volume market demands, intense price competition, operational cost efficiency, and medium-to-large-scale dominance. The proposed generic strategy map includes rigid consequences, strategic choices, and flexible consequences. These interconnected strategies provide MSMEs and industry players with a comprehensive framework to build competitive, sustainable, and innovative milk-based gelato businesses aligned with evolving market dynamics in Indonesia.